Negligible risk of the COVID-19 resurgence caused by work resuming in China (outside Hubei): a statistical probability study. (27th March 2020) - Zhao, Kedong; Long, Cheng; Wang, Yan; Zeng, Tieyong; Fu, Xinmiao
Abstract: The COVID-19 outbreak in China appears to reach the late stage since late March 2020, and a stepwise restoration of economic operations is implemented. Risk assessment for such economic restoration is of significance. Here, we estimated the probability of COVID-19 resurgence caused by work resuming in typical provinces/cities and found that such probability is very limited (<5% for all the regions except Beijing). Our work may inform provincial governments to make risk level-based, differentiated control measures.